THE EFFECTIVENESS OF USING CAKE APPLICATION TOWARDS STUDENTS’ LISTENING ABILITY IN JUNIOR HIGH SCHOOL - Nuraini, Amira; Syafrizal, Syafrizal; Fargianti, Yusti (TELL - US JOURNAL, 2025)
The aim of the study was to find out the use of Cake Application in improving the students’ listening ability at the seventh grade of SMPN 2 Sepatan. This research used quantitative research with a quasi-experimental approach. The researcher used experimental class and control class for the respondents. The researcher using Cake Application for experimental class while for Control class using conventional method. The population in this study were students of the class VII SMPN 2 Sepatan. The sample of this research were the students of class 7.3 included 35 students and class 7.4 included 35 students. The result showed that the t-test value of sig <0,01, it means that the p value <0.05. It was concluded that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. That means there were significant differences students’ listening ability before and after using the Cake Application. The research conducted shows that the use of Cake Application on students’ listening ability was effective.Keywords: Listening, Cake Application, Mobile Learning